The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.3390/v11100909
|View full text |Cite
|
Sign up to set email alerts
|

Reconstructing the Dissemination Dynamics of the Major HIV-1 Subtype B Non-Pandemic Lineage Circulating in Brazil

Abstract: Non-pandemic variants of the Human Immunodeficiency Virus Type 1 (HIV-1) subtype B accounts for a significant fraction of HIV infections in several Caribbean islands, Northeastern South American countries and the Northern Brazilian states of Roraima and Amazonas. In this paper, we used a comprehensive dataset of HIV-1 subtype B pol sequences sampled in Amazonas and Roraima between 2007 and 2017 to reconstruct the phylogeographic and demographic dynamics of the major HIV-1 subtype B non-pandemic Brazilian linea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 26 publications
3
4
0
Order By: Relevance
“…It is interesting to note that the B CAR (2.5-2.6) and B PAN (2.9-3.4) Amazonian clades reached similar highest median R e values. Furthermore, the highest median R e estimated here using a birth-death approach was comparable to the previous ones estimated for the B CAR−BR−I clade (3.8) using a coalescent-based approach (Arantes et al, 2019), but lower than those estimated for major B PAN Brazilian lineages spreading in the Southeastern region (5.0-7.9) (Mir et al, 2015). These findings support that differences in the spreading dynamics of subtype B lineages may reflect discrepancies in the connectivity of underlying transmission networks across different Brazilian states/regions, rather than intrinsic differences in viral transmissibility.…”
Section: Discussionsupporting
confidence: 79%
See 4 more Smart Citations
“…It is interesting to note that the B CAR (2.5-2.6) and B PAN (2.9-3.4) Amazonian clades reached similar highest median R e values. Furthermore, the highest median R e estimated here using a birth-death approach was comparable to the previous ones estimated for the B CAR−BR−I clade (3.8) using a coalescent-based approach (Arantes et al, 2019), but lower than those estimated for major B PAN Brazilian lineages spreading in the Southeastern region (5.0-7.9) (Mir et al, 2015). These findings support that differences in the spreading dynamics of subtype B lineages may reflect discrepancies in the connectivity of underlying transmission networks across different Brazilian states/regions, rather than intrinsic differences in viral transmissibility.…”
Section: Discussionsupporting
confidence: 79%
“…This finding is consistent with our BDSKY analyses that support a continuous expansion (R e > 1) of major B CAR and B PAN Amazonian clades over all the studied period. The BSKG model indicates a recent stabilization of some Amazonian B PAN clades since the late 2000s, and a previous study conducted by our group also indicated a recent epidemic stabilization of the clade B CAR−BR−I since the late 2000s (Arantes et al, 2019). Although the median estimated R e of the B CAR and B PAN Amazonian clades was somewhat lower between 2010 and 2018 (1.6-2.3) than during the previous decades (2.5-3.4), we found no solid evidence of epidemic stabilization or reduction in the BDSKY analyses.…”
Section: Discussionsupporting
confidence: 65%
See 3 more Smart Citations